Identification of key carbon emitters from the perspective of network analysis. (June 2023) - Xia, Lijuan; Li, Yongli; Ma, Xiaochen
Highlights: A multi-layer carbon flow network is constructed based on multi-region trade. This study constructs three indicators to assess carbon emission effects. This study reveals the mechanism of carbon emissions through network analysis. Abstract: Climate risks are sharpened and adaptation actions are urgent. However, the economic system is a whole composed of numerous interrelated and interactive economic elements and poses a challenge for carbon mitigation. To explore the carbon emission effects of producers in complex economic systems and formulate targeted carbon mitigation policies, this study constructs three indicators to assess the carbon emission effect embodied in the economy through network analysis. More specifically, the total emission effect of each producer is measured by the push-type effect and pull-type effect and tested by comparing with the hypothetical extraction method. Taking China as an example, the results show that the effect of different sectors on carbon emissions varies greatly. The production and distribution of electric power and heat power is a key sector dominated by the push-type effect. This is, its carbon emissions are mainly triggered by the demands of its downstream sectors. The total emission effects of Construction and Smelting and processing of metals are also strong, but their pull-type effect is dominant. According to the dominant effect in the total emission effect, we can draft targeted emission reduction strategies.